The Effects of Pro-Inflammatory Cytokines on Human Body and Their Relation with Diseases (Review Article) - Khalid Shaalan Sahab; Mohammed Asaad Mahdi; Ammar M. K. AL-Azzawi (ASJ - Academic Science Journal, 2023)
Cytokines are important mediators in inflammatory disorders that affect the entire body. Signaling molecules called pro-inflammatory cytokines, also known as inflammatory cytokines, are released by the immune system cells including macrophages and T helper cells (Th), which promote inflammation. Interleukin-1 (IL-1), Interleukin-6 (IL-6), and Interleukin- 12 (IL-12) are pro-inflammatory cytokines which are released during the inflammations. Other inflammatory cytokines are interleukin-18 (IL-18), interferon-gamma (IFN-γ), tumour necrosis factor-alpha (TNF-α), and granulocyte-macrophage colony-stimulating factor (GM-CSF) mediate the innate immune response. Immune cells, and activated macrophages release inflammatory cytokines to orchestrate inflammatory responses; however, continuous chronic inflammation release high levels of inflammatory cytokines creating inflammatory microenvironment that are associated with a variety of illnesses, including atherosclerosis, cancer, and other conditions. Although the quantity of inflammation caused by the production of pro-inflammatory cytokines is influenced by ageing, health preservation needs a balance between pro- and anti-inflammatory cytokines. Inflammatory diseases therapy employs monoclonal antibodies that can neutralize inflammatory cytokines or block their receptors. Conclusion: A review of previous research shows a strong correlation between cytokines and inflammatory diseases.